2018
DOI: 10.1002/mren.201800021
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Monte Carlo Simulation of Olefin Block Copolymers (OBCs) Produced via Chain‐Shuttling Polymerization: Effect of Kinetic Rate Constants on Chain Microstructure

Abstract: The ORCID identification number(s) for the author(s) of this article can be found under https://doi.org/10.1002/mren.201800021. PolyolefinsOlefin block copolymers (OBCs) are thermoplastic elastomers with unique statistical multiblock structures produced by chain-shuttling polymerization. In this study, a dynamic Monte Carlo model is used to simulate the effect of changing chain-shuttling (k CS ), catalyst deactivation (k d ), and chain transfer (k tr ) rate constants on the microstructure of OBCs made in a sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Since the discovery of chain shuttling polymerization leading to the commercial production of diblock and multiblock polyolefin copolymers, , it has drawn a significant amount of research interest. Olefin block copolymers have unique and advantaged properties rendering them useful for a number of applications. For instance, ethylene/1-octene multiblock copolymers exhibit a unique balance of high melting point and flexibility compared to random copolymers with a similar comonomer content. While simple metal alkyls are the most commonly used chain shuttling agents, effort is being made to design and synthesize more sophisticated chain shuttling agents (CSAs), such as dual-headed CSAs (DHCSAs), to access novel polymer architectures, such as telechelic and triblock polymers. Bickelhaupt et al reported the synthesis of difunctional cyclic zinc compounds using Rieke zinc and dibromoalkane .…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of chain shuttling polymerization leading to the commercial production of diblock and multiblock polyolefin copolymers, , it has drawn a significant amount of research interest. Olefin block copolymers have unique and advantaged properties rendering them useful for a number of applications. For instance, ethylene/1-octene multiblock copolymers exhibit a unique balance of high melting point and flexibility compared to random copolymers with a similar comonomer content. While simple metal alkyls are the most commonly used chain shuttling agents, effort is being made to design and synthesize more sophisticated chain shuttling agents (CSAs), such as dual-headed CSAs (DHCSAs), to access novel polymer architectures, such as telechelic and triblock polymers. Bickelhaupt et al reported the synthesis of difunctional cyclic zinc compounds using Rieke zinc and dibromoalkane .…”
Section: Introductionmentioning
confidence: 99%
“…In our previous publication, [20,22] the dynamic MC model was further extended to capture how the detailed microstructures OBC populations with a different number of blocks change during chain-shuttling polymerization in a semibatch reactor. However, the dynamic MC approach cannot apply directly to investigate the kinetics and microstructural evolution of OBCs during chain-shuttling polymerization in CSTR.…”
Section: Introductionmentioning
confidence: 99%
“…The lengths of the “hard” and “soft” segments are controlled by the kinetics of propagation and chain transfer at each catalyst center. Both high throughput experimentation (HTE) and kinetic modeling/simulation approaches have been used to better understand chain-shuttling polymerization. However, without the active catalyst concentrations, the absolute rates of propagation and chain transfer cannot be determined .…”
Section: Introductionmentioning
confidence: 99%